2008
DOI: 10.1038/ismej.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

The immediate environment during postnatal development has long-term impact on gut community structure in pigs

Abstract: The gastrointestinal tract of mammals contains a complex microbial community that influences numerous aspects of health and development. It is postulated that establishment of this community during early life has long-term consequences on the health status of adults. Potential influences on colonization are expected to include environmental microbes, diet and the developmental changes of the host. Denaturing gradient gel electrophoresis was used to follow the individual community dynamics of 24 piglets over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
171
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(193 citation statements)
references
References 45 publications
21
171
0
1
Order By: Relevance
“…The similarity of PCR-DGGE profiling was analyzed using Quantity One software with a match tolerance of 2% (Version 4.6.1; BIO-RAD Laboratories Inc., Hercules, CA, USA). Principal component analysis (PCA) was performed on the bandmatching matrix and Dice's similarity coefficient was calculated as previously described (Thompson et al, 2008).…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The similarity of PCR-DGGE profiling was analyzed using Quantity One software with a match tolerance of 2% (Version 4.6.1; BIO-RAD Laboratories Inc., Hercules, CA, USA). Principal component analysis (PCA) was performed on the bandmatching matrix and Dice's similarity coefficient was calculated as previously described (Thompson et al, 2008).…”
Section: Sample Collectionmentioning
confidence: 99%
“…The factors that determine the colonization rate and composition of the intestinal microbial species are not fully understood. Recent studies showed that there is no core microbiota shared by all individuals in humans, indicating that environmental exposure at an early stage of life may have an important role in shaping the intestinal microbiota (Thompson et al, 2008;Turnbaugh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount, composition and metabolism of these early colonizing microbial species in the gastrointestinal tract have a strong impact on the piglets' postnatal development (Mazmanian et al, 2005). The outcome of gut colonization in piglets is highly dependent on the microbial load of the environment and, therefore, influenced by hygiene measures (Thompson et al, 2008;Schokker et al, 2014). It was shown that the load with C. perfringens and E. coli in the early gut flora of newborn piglets was higher and of lower homogeneity compared with the gut flora at the end of the suckling period.…”
Section: Introductionmentioning
confidence: 99%
“…In the cow rumen, the complex strict anaerobic community develops only after weaning (Hungate, 1975). The colonization of the digestive tract can be affected by diet (Hidaka et al, 1986;Ito et al, 1990;Donovan and Odle, 1994), mode of delivery (Grö nlund et al, 1999) and environmental factors including stress (Bailey et al, 2004;Thompson et al, 2008), and the complex establishment of the organ microbiota can now be studied in due detail with powerful molecular tools. We hypothesized that mechanisms of bacterial succession occur in the crop during the transition from chicks to adults that develop the crop into a more complex and diverse ecosystem.…”
Section: Introductionmentioning
confidence: 99%